Health Potential of Clery Strawberries: Enzymatic Inhibition and Anti-Candida Activity Evaluation - Cairone, Francesco (Molecules, 2021)
Strawberries, belonging to cultivar Clery (Fragaria × ananassa Duchesne ex Weston) and to a graft obtained by crossing Clery and Fragaria vesca L., were chosen for a study on their health potential, with regard to the prevention of chronic and degenerative diseases. Selected samples, coming from fresh and defrosted berries, submitted to different homogenization techniques combined with thermal and microwave treatments, had been previously analyzed in their polyphenolic content and antioxidant capacity. In the present work, these homogenates were evaluated in relation to their enzymatic inhibition activity towards acetylcholinesterase and butyrylcholinesterase, α-amylase, α-glucosidase and tyrosinase. All these enzymes, involved in the onset of diabetes, and neurodegenerative and other chronic diseases, were modulated by the tested samples. The inhibitory effect on tyrosinase and cholinesterase was the most valuable. Antifungal activity against Candida albicans, recently shown to play a crucial role in human gut diseases as well as diabetes, rheumatoid arthritis and Alzheimer’s disease, was also shown in vitro and confirmed by the in vivo text on Galleria mellonella. Overall, the obtained results confirm once again the health potential of strawberries; however, the efficacy is dependent on high quality products submitted to correct processing flow charts.